Pengaruh Media Papan Jari Hitung terhadap Kemampuan Berhitung Siswa Kelas II A dan Kelas II B di SD Negeri 37 Cakranegara - Hayatul Nufus; Ida Ermiana; Asri Fauzi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Numeracy ability is one of the fundamental competencies in mathematics learning at the elementary school level, as it serves as the foundation for mastering more advanced mathematical concepts. However, in practice, there are still lower-grade students who experience difficulties in understanding basic arithmetic operations. Therefore, learning media that are concrete, engaging, and appropriate to students’ cognitive development stages are needed. This study aims to determine the effect of the Finger Counting Board Media on the numeracy ability of Grade II A and Grade II B students at SD Negeri 37 Cakranegara. This research employed a quantitative approach with a quasi-experimental design using the nonequivalent control group design type. The population of this study consisted of all Grade II students at SDN 37 Cakranegara, with a sample of 54 students, including 25 students from Class II A and 29 students from Class II B. Data collection techniques used were test and non-test methods. The instrument used in this research was a multiple-choice test sheet (Pretest and Posttest). Data analysis techniques included normality test, homogeneity test, hypothesis test, and N-gain test. The results of the study indicate that the use of finger counting board media has a significant effect on the numeracy ability of Grade II students. This is evidenced by the results of the independent sample test (t-test) with a sig (2-tailed) value of 0.000 (< 0.05), indicating that Ha is accepted and H0 is rejected. In addition, the N-Gain value obtained was 0.05.